2020
DOI: 10.1186/s40594-020-00255-y
|View full text |Cite
|
Sign up to set email alerts
|

A model of peer effects on instructor innovation adoption

Abstract: A considerable body of evidence demonstrates that active, student-centered instructional practices are more effective than lecture-based, transmissionist approaches in improving undergraduate STEM learning. Despite this evidence and extensive reform initiatives, the majority of STEM instructors continue to teach didactically. Awareness of teaching innovations is widespread in some STEM disciplines, and instructors report trying new instructional approaches, yet the majority of them fail to continue using activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 83 publications
(252 reference statements)
1
7
1
Order By: Relevance
“…Social norm showed no direct effect on behavioral intent or indirect effect on behavior, indicating that instructors' perceptions of support from colleagues had no measurable impact on their intent to use IBL nor their intensity of use of IBL methods. This finding is inconsistent with prior research that has shown linkages between department culture or support and RBIS use [16,62] However, this finding is consistent with prior research using the TPB, where social norms typically have weak associations to behavioral intent [32]. One explanation for this finding is that many of the workshop participants received financial support from their department or institution to attend the conference, thus were less likely to perceive lack of support as barrier to RBIS use.…”
Section: Plos Onecontrasting
confidence: 96%
“…Social norm showed no direct effect on behavioral intent or indirect effect on behavior, indicating that instructors' perceptions of support from colleagues had no measurable impact on their intent to use IBL nor their intensity of use of IBL methods. This finding is inconsistent with prior research that has shown linkages between department culture or support and RBIS use [16,62] However, this finding is consistent with prior research using the TPB, where social norms typically have weak associations to behavioral intent [32]. One explanation for this finding is that many of the workshop participants received financial support from their department or institution to attend the conference, thus were less likely to perceive lack of support as barrier to RBIS use.…”
Section: Plos Onecontrasting
confidence: 96%
“…How universities can best apply these to further adoption methods, or mandate technology usage as a term of employment, requires further observation, particularly regarding hybrid instruction. Further, we agree with McConnell et al (2020) that research on the relationship between instructional staff information exchange and technology adoption is needed. Results would allow universities to better develop future decision making and adoption processes, particularly as higher education enters the metaverse.…”
Section: Suggestions For Further Research and Conclusionsupporting
confidence: 69%
“…Students receiving validation by having their ideas accepted and valued by peers and teachers demonstrates important contributions (McConnell, 2020;Salomone, 2017); as such, opportunities to problem solve and succeed increase a student's self-efficacy in education and in that field and increase their motivation to persist (Mistele et al, 2019;Zavala & Hand, 2019).…”
Section: Problem Statementmentioning
confidence: 99%
“…This mismatch of pedagogical approaches creates gaps where such students feel alienated because the biological sciences require a different method of rigorous reasoning to achieve a level of proficiency in the subject. Therefore, creating peer mentor collaborative problem-based learning with a cohort of interdisciplinary students would ensure students succeed in their I-STEM education through positive interactions with their peers and curricular content (Langer-Osuna, 2017;McConnell et al, 2020).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation